Sedimentology and evolution of the Holocene radial tidal sand ridge in the south Yellow Sea, China - He, Lei; Ye, Siyuan; Xue, Chunting; Zhao, Guangming; Yang, Shixiong; Amorosi, Alessandro (Frontiers in Earth Science, 2023)
The radial tidal sand ridge (RTSR) off Jiangsu coast in the South Yellow Sea is one of the fantastic and unique natural landscapes around the world. A large amount of investigations on geomorphology and marine geology have been implemented during the last several decades. The formation and evolution of the RTSR, however, are still under debate. To resolve this issue, ten ~30–60 m-long cores were retrieved from the Jiangsu coastal plain and offshore sand ridge field in 2018-2019. Stratigraphic transects chronologically constrained by abundant radiocarbon dates were built based upon sedimentological and paleoecological (i.e., foraminifer) data from selected cores. Combined with well-documented core stratigraphy from earlier studies, an age-depth plot with a local sea-level change curve revealed that the RTSR initiated approximately 9000 cal a BP in a sandy bedform shape under transgressive conditions, continued throughout the Holocene, but developed mostly after 1128 AD, when the Yellow River flowed southwards into the Yellow Sea. Abundant sediment supply, thus, appears to have played a major role in the formation and evolution of the RTSR in the South Yellow Sea.